The world food outlook - Mitchell, Donald O. (Trade and development (Cambridge, England), 1997)
"Modern-day Malthusians warn that Malthus will ultimately be right: the world will be less and less able to feed itself. They are anxious to apply their pessimism to developing countriespopulation keeps expanding, no new land is being created, crop yields have increased considerably and may have peaked, and the environment may not tolerate the pressure of more intensive agriculture. While these arguments seem persuasive, the evidence to the contrary is compelling: prices of agricultural commodities in real terms are at their lowest level in history, and crop output continues to rise faster than population." "The fact is that the world food situation has improved dramatically for most of the world's consumers. Not all people in the world today have adequate diets and there is no doubting the desperate circumstances of some peoples, but diets for most of the world's consumers have improved dramatically and per capita calorie consumption in developing economies has increased by some 27 per cent since the 1960s. It should continue to improve, and food will be cheaper than it is today." "Sub-Saharan Africa remains the primary exception to these general developments with stagnant or even declining per capita consumption levels. There are serious problems of hunger and malnutrition. But here the problems extend well beyond agriculture."--Jacket